Effect of thickness of CuI hole injection layer on properties of organic light emitting diodes - Hotra, Zenon; Stakhira, Pavlo; Cherpak, Vladyslav; Volynyuk, Dmytro; Voznyak, Lesya; Gorbulyk, Volodymyr; Tsizh, Bogdan (Photonics Letters of Poland, 2012)
We report the influence of the thickness of a copper iodide (CuI) hole injection layer (HIL) on the performance of organic light-emitting diodes (OLEDs) with tris-8-hydroxyquinoline aluminum (Alq3) active layer and aluminum cathode layer. The investigation of structural and morphological properties of thermally evaporated CuI thin films indicates that they are amorphous. OLEDs with the ITO/CuI/Alq3/poly(ethylene glycol) dimethyl ether/Al structures were fabricated and current density-voltage, luminance-voltage and current efficiency-current density were analyzed. The maximal luminescence current efficiency is obtained for the devices with a CuI thickness of 12nm. Full Text: PDF References: W. Brütting, S. Berleb, A.G. Mückl, "Device physics of organic light-emitting diodes based on molecular materials", Organic Electronics 2, 1 (2001).CrossRef H. Kubota et al., "Organic LED full color passive-matrix display", Journ. of Lumin. 87-89, 56 (2000).CrossRef J. Kido, "Organic displays", Phys. World 12, 27 (1999).DirectLink M. Stossel, J. Staudigel, F. Steuber, J. Simmer, A. Winnacke, "Impact of the cathode metal work function on the performance of vacuum-deposited organic light emitting-devices", Appl. Phys. A: Mater. Sci. Process 68, 387 (1999).CrossRef T.M. Brown, R.H. Friend, I.S. Millard, P.J. Lacey, J.H. Burroughes, F. Cacialli, "Efficient electron injection in blue-emitting polymer light-emitting diodes with LiF/Ca/Al cathodes ", Appl. Phys. Lett. 79, 174 (2001).CrossRef B. Choi, H. Yoon, H.H. Lee., "Surface treatment of indium tin oxide by SF6 plasma for organic light-emitting diodes ", Appl. Phys. Lett. 76, 412 (2000).CrossRef K. Fehse, G. Schwartz, K. Walzer, K. Leoa, "Combination of a polyaniline anode and doped charge transport layers for high-efficiency organic light emitting diodes", J. Appl. Phys. 101, 124509 (2007).CrossRef N. Drolet, S. Beaupré, J.F. Morin, Y. Tao, M. Leclerc, "Red–green–blue light-emitting diodes containing fluorene-based copolymers", J. Optic Pure Appl Optic 4, S252 (2002).CrossRef B.D. Chin, "Role of the polymeric hole injection layer on the efficiency and stability of organic light emitting diodes with small molecular emitters", J Phys D: Appl Phys. 41, 215104 (2008).CrossRef S.A. Van Slyke, C.H. Chen, C.W. Tang., "Organic electroluminescent devices with improved stability", Appl. Phys. Lett. 69, 2160 (1996).CrossRef Y. Shen, D.B. Jacobs, G.G. Malliaras, G. Koley, M.G. Spencer, A. Ioannidis, "Modification of Indium Tin Oxide for Improved Hole Injection in Organic Light Emitting Diodes", Adv. Mater 13, 1234 (2001).CrossRef C. Qiu, Z. Xie, H. Chen, M. Wong, H.S. Kwok, "Comparative study of metal or oxide capped indium–tin oxide anodes for organic light-emitting diodes", J. Appl. Phys. 93, 3253 (2003).CrossRef P.Y. Stakhira, V.V. Cherpak, "The properties of heterojunction based on CuI/pentacene/Al", Vacuum 83, 1129 (2009).CrossRef P. Stakhira, V. Cherpak, D. Volynyuk, F. Ivastchyshyn, Z. Hotra, V. Tataryn, G. Luka, Thin Solid Films. 518, 7016 (2010)., "Characteristics of organic light emitting diodes with copper iodide as injection layer".CrossRef P.M. Sirimanne, T. Soga, M. Kunst,"Observation of microwave conductivity in copper iodide films and relay effect in the dye molecules attached to CuI photocathode", J. Solid. State Chem. 178, 3010 (2005).CrossRef T.H. Lee et al., Adv. Funct. Mater. 18, 3036 (2008), "Organic-Oxide Cathode Buffer Layer in Fabricating High-Performance Polymer Light-Emitting Diodes", .CrossRef T.F. Stoica et al., "Characterization of ITO thin films prepared by spinning deposition starting from a sol-gel process", J. Optoelectron. Adv. Mater. 2, 684 (2000).DirectLink T. Maruyama, K. Fukui, "Indium-tin oxide thin films prepared by chemical vapor deposition", J. Appl. Phys. 70, 3848 (1991).CrossRef Y. Shirota et al., "Multilayered organic electroluminescent device using a novel starburst molecule, 4,4′,4″?tris(3?methylphenylphenylamino)triphenylamine, as a hole transport material", Appl. Phys. Lett. 65, 807 (1994).CrossRef Ch. Jonda, A.B.R. Mayer, U. Stolz, A. Elschner, A. Karbach, "Surface roughness effects and their influence on the degradation of organic light emitting devices ", J. Mater. Sci. 35, 5645 (2000).CrossRef A.V. Kukhto, "Electroluminescence of Thin Films of Organic Compounds (Review)", J. Appl. Spectrosc. 70, 165 (2003).CrossRef P.M. Sirimanne, M. Rusop, T. Shirata, T. Soga, T. Jimbo, "Characterization of transparent conducting CuI thin films prepared by pulse laser deposition technique", Chem. Phys. Lett. 366, 485 (2002).CrossRef J. Shinar, Organic light-emitting devices: a survey (New York, Springer 2004).